Chemical constituents from the leaves of psidium guajava linn. and their chemotaxonomic significance. Issue 2 (17th January 2023) - Zhou, Guangxin; Zhao, Jiaming; Gong, Chang; Xu, Jixuan; Song, Ce; Meng, Dali
Abstract: The phytochemical investigation on the leaves of Psidium guajava Linn. led to the isolation and identification of 18 compounds, including six guavinoside (1-6 ), four flavonoids (7-10 ), eight triterpenoids (11-17 ) and one lignans (18 ). All chemical structures were elucidated via NMR spectroscopic methods, and further supported by comparison with literature data. Compounds 12, 14, 16 and 18 was isolated from the Myrtaceae family for the first time. The chemotaxonomic significance of these compounds was also discussed based on their structure types, as well as compounds-genus/family network analysis. The results showed that there were close chemotaxonomic relationships among the Myrtaceae, Asteraceae, and Lamiaceae families. Guavinosides A-F could be considered as valuable chemotaxonomic markers of Myrtaceae family, while guavinosides C-F might serve as chemotaxonomic markers for distinguishing the P. guajava . Graphical Abstract: UF0001